34. SAFETY OF USING SINGLE-NUCLEAR CELL CONTAINING STEM CELLS FROM THE AUTOLOGOUS BONE MARROW IN TREATING CHILDREN WITH CEREBRAL PALSY DUE TO ASPHYXIA IN VINMEC TIMES CITY HOSPITAL (Vietnam Journal of Community Medicine, 2023)
Objective: Research using single -nuclear cell containing stem cells from autologous bone marrow in treating children with cerebral palsy due to brain hypoxia at birth was accepted at the Ministry of Science and Technology in September 2018. Initial results showed safety and evidence of effectiveness. The objective of this study is to confirm the safety of a single -nuclear cell containing stem cells from autologous bone marrow on a larger sample size in children with cerebral palsy due to asphyxia at birth. Subjects and methods: This is a restrospective-perspective combined conducted in more than 50 cerebral palsy patients due to asphyxia that has been infused the single cell containing stem cells from the autologous bone marrow at Vinmec International Hospital. The Safety was assessed during the first and second transfusion and throughout the 12-month study period. Results: There were no serious adverse events identified as associated with transfusion of single -nuclear cell containing stem cells from autologous bone marrow in treating children with cerebral palsy due to brain hypoxia. Conclusion: Using single -nuclear cell masses containing stem cells from the autologous bone marrow in the treatment of children with cerebral palsy due to asphyxia is safe.
Keywords: Stemcell, cerebral palsy.